1982
DOI: 10.1111/j.1348-0421.1982.tb00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Disorders of Serum Lipoproteins in Endotoxin‐Poisoned Mice: The Role of High Density Lipoprotein (HDL) and Triglyceride‐Rich Lipoproteins

Abstract: A study was performed to clarify the role of serum lipoproteins, especially high density lipoprotein (HDL) and triglyceride-rich lipoproteins in endotoxemic or endotoxin-poisoned animals. The level of HDL-cholesterol decreased markedly in mouse serum 18-24 hr postintoxication, while the amount of low density lipoprotein (LDL)-cholesterol in the sera of poisoned mice was about 175% of that of the controls. Serum lecithin-cholesterol acyltransferase activity in the poisoned mice decreased slightly for 3-6 hr aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
24
0
1

Year Published

1983
1983
2000
2000

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 46 publications
2
24
0
1
Order By: Relevance
“…A number of reports are now available which show that suppression of LPL activities in adipose tissue, heart or post-heparin plasma resulting in hypertriglyceridemia occurs in infections or endotoxemia (1,3,8,9,(12)(13)(14). However, changes in H-TGL under such conditions are not well established.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of reports are now available which show that suppression of LPL activities in adipose tissue, heart or post-heparin plasma resulting in hypertriglyceridemia occurs in infections or endotoxemia (1,3,8,9,(12)(13)(14). However, changes in H-TGL under such conditions are not well established.…”
Section: Discussionmentioning
confidence: 99%
“…From these reports, differences might also be expected between the effect of endotoxin on either H-TGL or LPL activity. Sakaguchi (14) recently showed a slight increase in H-TGL activity after injection of endotoxin from Salmonella typhimurium in mice. Our data, however, show clearly that the activity of H-TGL as well as that of LPL was decreased in animals treated with endotoxin from E. coli.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sakaguchi (8) reported that serum ex-lipoprotein (HDL) in the electrophoretic patterns was reduced according to the dosage of endotoxin given 18 hr postintoxication, and that the fraction in mice injected with lead acetate plus endotoxin was markedly lower than that mice given in the endotoxin alone. Freudenberg et al (2) surmised that HDL represents a transport protein for LPS in plasma to organs of clearance or to other cellular targets, and that LPS interacts with plasma HDL, forming a complex with characteristic electrophoretic mobility.…”
mentioning
confidence: 99%